KEHIDUPAN SOSIAL EKONOMI PETANI KARET DI DESA PENARAH KECAMATAN BELAT KABUPATEN KARIMUN - Muhamad Nizam; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at Penarah Kecamatan Belat Kabupaten Karimun which aims to learn the socio-economic life of the rubber farmers at Penarah. This research entitled “The Socio-Economic Life of Rubber Farmers at Penarah Kecamatan Belat Kabupaten Karimun” The prime problem of this research is to learn the socio-economic condition of the rubber farmers at Penarah during the decreasing of rubber prices and the way to survive. The population of this research is all of the rubber farmers at Penarah and the sample of this research is 50% of the total population that is 83 farmers. This research used simple random sampling in selecting the sample. This is a quantitative and descriptive research. The data of his research was obtaied by conducting an interview, distributing the questionnaire, doing an observation and recording the documentation. The analysis of this research is tabulated and explained. Theories used in this research are social action income and survival strategy. According to the result of this research, it can be concluded that the socio-economic life of the rubber famers at Penarah in terms of income is decreasing but it can be solved by implementing survival strategy which are active, passive and networking strategy.Keywords : Rubber farmers, Socio-economic, Survival strategy